2014
DOI: 10.1016/j.jmbbm.2013.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and diameter dependent viscoelastic properties of mitral valve chordae tendineae

Abstract: This study aimed to characterise viscoelastic properties of different categories of chordae tendineae over a range of frequencies. Dynamic Mechanical Analysis (DMA) was performed using a materials testing machine. Chordae (n=51) were dissected from seven porcine hearts and categorised as basal, marginal, strut or commissural. Chordae were loaded under a sinusoidally varying tensile load at a range of frequencies between 0.5 and 5Hz, both at a standardised load (i.e. same mean load of 4N for all chordae) and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(89 citation statements)
references
References 53 publications
10
75
4
Order By: Relevance
“…16 In terms of simulating occlusal load under physiological or traumatic conditions, the present study used DMA to interpret the dynamic tensile properties of the human PDL in a frequency range of 0.1 and 10 Hz. The results of the present study were consistent with those reported before, 10,11 in which the measured storage and loss moduli increased as a function of frequency, but tand showed small variation with the frequency. In comparison to the dynamic shear properties of porcine PDL, 17 the dynamic modulus in the present study was higher at comparable frequencies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…16 In terms of simulating occlusal load under physiological or traumatic conditions, the present study used DMA to interpret the dynamic tensile properties of the human PDL in a frequency range of 0.1 and 10 Hz. The results of the present study were consistent with those reported before, 10,11 in which the measured storage and loss moduli increased as a function of frequency, but tand showed small variation with the frequency. In comparison to the dynamic shear properties of porcine PDL, 17 the dynamic modulus in the present study was higher at comparable frequencies.…”
Section: Discussionsupporting
confidence: 93%
“…Since the 1990s, dynamic mechanical analysis (DMA) has been used to investigate the viscoelastic properties of biological tissue, such as lens, 8 articular cartilage, 9 cardiovascular tissue, 10 bladder tissue, 11 and so on. The frequency dependency of the storage (E 0 ) and loss (E 00 ) moduli of various biomaterials was obtained from DMA testing.…”
Section: Introductionmentioning
confidence: 99%
“…While much of this range of frequencies may not appear physiological, characterisation of natural tissues should consider not only physiological rates of loading, but also loading associated with exercise, other daily activities, pathophysiology and/or trauma [23,24,35]. However, loading rates and equivalent frequencies associated with loading of the upper-limb/elbow, and of potential relevance to the ulnar nerve are less well understood than, say, for natural tissues such as for heart valves [35][36][37] or lower limbs [23,38,39]. However, there are upper-limb studies which suggest that frequencies of 20 repeats/min (0.33 Hz) are associated with discomfort levels within a physiological loading range [40], providing a lower range for an experimental loading frequency.…”
Section: Resultsmentioning
confidence: 99%
“…68 It is challenging to model the mechanical behaviour of the MV accounting for all the anisotropic and nonlinear behaviour; the coupling between different directions, the differences of in vivo and ex vivo, and the residual strain and strain-path dependence. The MV material properties are mainly derived from animal heart valvular experiments 17,[69][70][71][72][73][74][75][76] . In uniaxial studies of excised leaflets, Kunzelman and Cochran 17 measured the stress-strain behaviour of MV within distinct pretransitional and posttransitional regions.…”
Section: Materials Modelsmentioning
confidence: 99%